THE TRANSFORMATIVE ROLE OF ARTIFICIAL INTELLIGENCE IN THE AGRICULTURAL SECTOR - Ihnatko, Mariia (SWorld-Ger Conference proceedings, 2024)
The article examines specific aspects of applying Artificial Intelligence (AI) technologies in the agricultural sector. It identifies key areas for the active implementation of AI within the industry. A forecast for global economic growth by 2035 is prese